PENGHENTIAN TINDAKAN MEDIS YANG DAPAT DIKUALIFIKASIKAN SEBAGAI EUTHANASIA - Nurdiyanningrum, Galih (Jurnal Panorama Hukum, 2018)
The studies of Euthanasia is interesting to be discuss, how about the law regulation in Indonesia, specially the concept of Pasif Euthanasia connecting with stopping medical act based on Informed Consent from patient or their family which done by the doctor and law effect for the doctor. This study is a normatif research with statute approach and conceptual approach. In this thesis, the writer focussing her study in stopping medical act which can be classified as Euthanasia is stopping the medicines, medical treatment and ignoring the patient. The purpose of this thesis is to research in dept that informed consent from patient or their family is use to prevent the doctor from the law impact cause by the stopping Medical Act. The role of doctor is very important in giving suggestion, solution and try to give the emphaty to the patient before they decided to stop the Medical Act to themselves. Hopefully this thesis can give a new paradigma and beneficial enough to the reader.